Implementation of Learning the Book of Taudhihus Prayer and Matan Jurumiyah at Students of Al-Barokah Islamic Boarding School Kemuja Bangka - Mega, Mega; Hasan, Subri; Jauhari, Muhammad Insan (LENTERNAL: Learning and Teaching Journal, 2025)
The implementation of the Taudhihus Sholat and Matan Jurumiyah Book Learning has included planning, implementation, and evaluation. The main objective of this implementation is to improve the religious understanding of female students, so that they not only master the theory, but are also able to practice it in their daily lives according to Islamic teachings. This type of research is field study or qualitative research, namely describing and describing objects that are in accordance with what is in the field. The data sources consist of primary data and secondary data. Data collection through observation, interview and documentation methods. The results of this study are 1) Learning planning is carried out flexibly and contextually without written administrative tools, with a focus on understanding the contents of the book by teachers, determining objectives, determining materials, and using traditional pesantren methods such as bandongan or wetonan. 2) The implementation of learning takes place in stages and interactively, with an emphasis on adjusting the material to the abilities of female students and providing a question and answer space, in order to deepen understanding both in terms of language through the Matan Jurumiyah Book and aspects of worship through the Tawdihus Sholat Book. 3) Learning evaluation is carried out comprehensively through written, oral, and practical exams, and is equipped with a remedial program for female students who have not reached the standard, to strengthen understanding, increase critical thinking, and shape the character of female students who are able to practice knowledge in everyday life.